Some Hematological and Blood Biochemical Profile of Iraqi Riverine Buffaloes (Bubalus bubalis) During Different Gestation Periods - Abdulkareem, Talal A. (Journal of Buffalo Science, 2013)
This study was conducted to demonstrate some hematological and blood biochemical profile of Iraqi riverine buffaloes (Bubalus bubalis) during pregnancy. Ten out of 22 adult buffaloes of 4.6 ± 0.97 years old were used in this study. Blood samples was collected from each buffalo from mating (day 0), day 22-24 PM, 10-12 days interval during gestation period. Hemoglobin (Hb) was greater (P < 0.05) at days 103 – 106, 133 – 136 and 238 – 241 of pregnancy than those at 32 -34 days PM. The AST was highest at days 133 – 136 of pregnancy. Higher and lower ALP activity was noted at days 178-181 of gestation. A considerable increase in plasma albumin occurred at days 268–271 of gestation in comparison to days 42 – 44 PM. In conclusion, nutritional deficiencies and metabolic disorders during gestation in riverine buffaloes can be detected by monitoring blood alterations.